2020
DOI: 10.1073/pnas.2005111117
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between 15-lipoxygenase and secreted PLA 2 promotes inflammation by formation of TLR4 agonists from extracellular vesicles

Abstract: Damage-associated endogenous molecules induce innate immune response, thus making sterile inflammation medically relevant. Stress-derived extracellular vesicles (stressEVs) released during oxidative stress conditions were previously found to activate Toll-like receptor 4 (TLR4), resulting in expression of a different pattern of immune response proteins in comparison to lipopolysaccharide (LPS), underlying the differences between pathogen-induced and sterile inflammation. Here we report that synergistic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Infections activate the immune system, triggering the inflammatory cascade. It was recently reported that during inflammation two enzymes are induced: 15-lipoxygenase (15-LO) and secreted phospholipase A 2 (sPLA 2 ) [ 58 ]. Notably, 15-LO is expressed in human podocytes [ 59 ], while sPLA 2 is expressed in platelets, neutrophils, eosinophils, and macrophages [ 60 ].…”
Section: Podocyte Physiopathology and Infectionsmentioning
confidence: 99%
“…Infections activate the immune system, triggering the inflammatory cascade. It was recently reported that during inflammation two enzymes are induced: 15-lipoxygenase (15-LO) and secreted phospholipase A 2 (sPLA 2 ) [ 58 ]. Notably, 15-LO is expressed in human podocytes [ 59 ], while sPLA 2 is expressed in platelets, neutrophils, eosinophils, and macrophages [ 60 ].…”
Section: Podocyte Physiopathology and Infectionsmentioning
confidence: 99%
“…Additionally, the increased expression of some of these inflammatory molecules is dependent on nuclear factor κB activation [ 15 , 16 ]. Moreover, recently it has been reported that 15-LOX may interact with secretory phospholipase A2 (sPLA2), contributing to sterile inflammation in chronic conditions with differences from classical inflammation on the cytokine level [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al proposed that oxidative stress-EVs are distinct from lipopolysaccharide (LPS)-induced EVs. They activate Toll-like receptor 4 (a type of DAMP) via synergy between 15-lipoxygenase and secreted PLA 2, resulting in aseptic inflammation [ 57 ], which offers a new opportunity to limit aseptic inflammation. Raffaele et al found that in the dorsal root ganglion (DRG), neuronal-immune crosstalk can be mediated by neuronal exosomes taken up by macrophages, which initiate a feedback loop of elevations in ROS and exosomes, propagating long-term pain [ 99 ].…”
Section: 'Accomplice'——evs In the Pathogenesis Of Osteoarthritismentioning
confidence: 99%